Biochemical characterization of a novel thermostable xyloglucanase from an alkalothermophilic thermomonospora sp. - Pol, Dipali; Menon, Vishnu; Rao, Mala (Extremophiles, 2012)
Xyloglucanase from an extracellular culture filtrate of alkalothermophilic Thermomonospora sp. was purified to homogeneity with a molecular weight of 144 kDa as determined by SDS-PAGE and exhibited specificity towards xyloglucan with apparent K (m) of 1.67 mg/ml. The enzyme was active at a broad range of pH (5-8) and temperatures (40-80A degrees C). The optimum pH and temperature were 7 and 70A degrees C, respectively. The enzyme retained 100% activity at 50A degrees C for 60 h with half-lives of 14 h, 6 h and 7 min at 60, 70 and 80A degrees C, respectively. The kinetics of thermal denaturation revealed that the inactivation at 80A degrees C is due to unfolding of the enzyme as evidenced by the distinct red shift in the wavelength maximum of the fluorescence profile. Xyloglucanase activity was positively modulated in the presence of Zn2+, K+, cysteine, beta-mercaptoethanol and polyols. Thermostability was enhanced in the presence of additives (polyols and glycine) at 80A degrees C. A hydrolysis of 55% for galactoxyloglucan (GXG) from tamarind kernel powder (TKP) was obtained in 12 h at 60A degrees C and 6 h at 70A degrees C using thermostable xyloglucanases, favouring a reduction in process time and enzyme dosage. The enzyme was stable in the presence of commercial detergents (Ariel), indicating its potential as an additive to laundry detergents.
Keywords: Alkalothermophilic Thermomonospora sp.; Biotechnological applications; Purification; Thermostable; Xyloglucanase